Valuing nature-based recreation in forest areas in Italy: An application of Travel Cost Method (TCM). (1st January 2023) - Alessandro, Paletto; De Meo, Isabella; Grilli, Gianluca; Notaro, Sandra
Abstract: Nature-based recreation provides benefits facilitating social interactions and cohesion, creating job opportunities, and stimulating the local economy. The aim of this study was to assess the recreational economic value of different forest areas considering two aspects: stand features and proximity of the forest to urban areas. An individual Travel Cost Method (TCM) was applied in three study areas in Italy involving 603 visitors in the survey. The results show that in all three case studies the most important forest-based recreational activity carried out by visitors is hiking, followed by picnicking and mountain biking. The TCM estimates a consumer surplus between €7.33 and €17.37 per visit. The key points highlighted by the study are that: managed natural forests have a higher recreational economic value than unmanaged artificial forests; the peri-urban forests are characterized by a higher number of visitors but a lower value per visit than mountain forests.